2021
DOI: 10.31234/osf.io/kcdt5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metacognition in second language speech perception and production

Abstract: Metacognition is the ability to monitor and control one's own cognition and behaviour. However, the role of metacognition in language remains poorly understood. Here we investigated metacognitive processing in non-native language perception and production, by asking participants to rate, on a trial-by-trial basis, their self-confidence in the accuracy in a phoneme identification and production task. The results revealed metacognitive ability in perception, as participants' confidence judgments aligned with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 51 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…However, it is not impossible that native Spanish speakers’ rounding of these vowels (revealed by the third formant, F3) differed from that implemented by native French speakers, and adding this cue in the accuracy measure would have increased the strength of the perception–production relationship (see Llompart & Reinisch, 2018, for work on the role of acoustic cues in L2 perception). To examine this possibility and the role of F3 in the production of this novel contrast, we ran a series of analyses (available in the project's OSF profile at https://osf.io/usrdw, see also Kartushina et al., 2022a), that revealed: (a) no difference in F3 between Spanish and native French groups, nor interaction between group and vowel, (b) no correlation between the F3‐distance to the norms (participants’ F3 and native French speakers’ F3) and the confidence rating, and (c) no correlation between the F3‐distance to the norms and participants’ identification accuracy for either vowel. These additional analyses suggested that, similar to native speakers of French, Spanish participants did not use F3, a roundness cue, to distinguish between the two French vowels and that the accuracy in F3 (alone) was not related to the participants’ contrast perception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is not impossible that native Spanish speakers’ rounding of these vowels (revealed by the third formant, F3) differed from that implemented by native French speakers, and adding this cue in the accuracy measure would have increased the strength of the perception–production relationship (see Llompart & Reinisch, 2018, for work on the role of acoustic cues in L2 perception). To examine this possibility and the role of F3 in the production of this novel contrast, we ran a series of analyses (available in the project's OSF profile at https://osf.io/usrdw, see also Kartushina et al., 2022a), that revealed: (a) no difference in F3 between Spanish and native French groups, nor interaction between group and vowel, (b) no correlation between the F3‐distance to the norms (participants’ F3 and native French speakers’ F3) and the confidence rating, and (c) no correlation between the F3‐distance to the norms and participants’ identification accuracy for either vowel. These additional analyses suggested that, similar to native speakers of French, Spanish participants did not use F3, a roundness cue, to distinguish between the two French vowels and that the accuracy in F3 (alone) was not related to the participants’ contrast perception.…”
Section: Discussionmentioning
confidence: 99%
“…We used a two-tailed alpha level of .05 to establish significance for all statistical tests. Experimental data, stimuli, experimental software, and analysis scripts are available on IRIS (Kartushina et al, 2022a(Kartushina et al, , 2022b(Kartushina et al, , 2022c and via the OSF (https://osf.io/usrdw).…”
Section: Statistical Modelingmentioning
confidence: 99%
See 1 more Smart Citation